European Integration and the Governance of Higher Education and Research
XI, 309 p.
Keywords: Given the overall ambitions and goals of the Lisbon agenda and the Bologna process, and other relevant supranational and intergovernmental European integration processes, it is obvious that these processes are intended to affect the university in all its basic structural features, including the way it performs its basic activities. However, the European Commission does not have formal authority with respect to the university, nor did the governments that signed the Bologna process develop an executive administrative capacity for implementing the Bologna Declaration. As a consequence, whether and how the supranational and intergovernmental European integration processes actually affect university governance and the university as a social institution is far from clear. The authors of this volume have dedicated considerable effort to the analysis of the Bologna process implementation. They offer a unique and critical view of the nature and possible effects of these very complex processes.